OS-MRS as a predictor of hospital length of stay – a retrospective audit of patients submitted to elective gastric bypass surgery - Cruz, Fátima (2021)
Background: Obesity is an important public health problem, with a high prevalence worldwide. Bariatric surgery emerged as an effective therapeutic tool, with improvement of quality of life and a decrease in all-cause mortality. Obesity Surgery Mortality Risk Score (OS-MRS) predicts 90-day mortality after bariatric surgery, but its association with hospital length of stay (LOS) has not been elucidated. We aimed to evaluate the association between OS-MRS and LOS after gastric bypass surgery. Methodology: We retrieved clinical and demographic data of 474 patients who had been submitted to gastric bypass surgery for this retrospective audit at Hospital de Santo António, Centro Hospitalar Universitário do Porto, Porto, (Portugal), between January 2010 and May 2015. The patients were classified as Class A, B or C. The primary goal was to evaluate whether there was an association between OS-MRS and LOS after gastric bypass surgery. The study of the relationship between duration of surgery (DS) and LOS was also performed. Results: After application of exclusion criteria, 402 patients were included in the statistical analysis (172 patients Class A, 187 Class B and 43 Class C). Patients classified as OS-MRS Class A had a significant shorter LOS (3.5 ± 2.3 days) than patients classified as Class B (4.2 ± 5.1 days) and Class C (5.7 ± 12.6 days; p<0.001). A significant positive correlation between DS and LOS was observed, although the degree of that correlation was weak (ρ=0.203; p=0.001). Conclusion: A positive association of OS-MRS with hospital length of stay and duration of surgery was observed; the patients with higher OS-MRS classes had longer length of stay in the hospital and longer duration of surgery. Moreover, longer length of stay was slightly associated with longer surgery duration.